Peranan media pembelajaran dalam pengajaran Bahasa Arab - Mabruroh, Lu’lu’atul (Maliki Interdisciplinary Journal, 2023)
The role of learning media is very important in a process of teaching Arabic. The learning media used will greatly influence a student’s learning success and increase student learning achievement. Learning media consists of various types, such as sam’iyah, audio-visual, or images, which have a function in increasing student activity in the learning process. In its use, learning media makes it very easy for a teacher to deliver a material to increase the effectiveness of student learning. Therefore, research on the use of instructional media in the process of teaching Arabic is very influential in improving the quality of learning Arabic. From several studies have shown the importance of learning media in improving student learning outcomes as well as being an easy tool for teachers in delivering a material.